2022
DOI: 10.1590/1519-6984.236297
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterization and biological activities of Plectranthus barbatus Andrews

Abstract: Plectranthus barbatus Andrews (Lamiaceae) is widely distributed in the world and has a range of popular therapeutic indications. This work aimed to evaluate the phytochemical characterization of two leaf extracts of P. barbatus, and their antimicrobial, antineoplastic and immunomodulatory potential. After collection, herborization and obtainment of the P. barbatus aqueous extract (PBA) and acetone:water 7:3 P. barbatus organic extract (PBO), the phytochemical characterization was performed by high-performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…Mothana et al [30], evaluating the antibacterial potential of Plectranthus species, demonstrated the inhibitory potential of P. barbatus and its hexanic, chloroformic, and butanolic fractions against Gram-positive strains with MIC ranging from 62.5 to 312.5 µg/mL, corroborating the results obtained. The aqueous and aqueous aceto extracts of P. barbatus leaves showed MIC against E. coli, P. aeruginosa and two strains of MRSA ≥ 500 µg/mL, showing lower effectiveness than the extract under study [9].…”
Section: Antimicrobial Activitymentioning
confidence: 70%
See 1 more Smart Citation
“…Mothana et al [30], evaluating the antibacterial potential of Plectranthus species, demonstrated the inhibitory potential of P. barbatus and its hexanic, chloroformic, and butanolic fractions against Gram-positive strains with MIC ranging from 62.5 to 312.5 µg/mL, corroborating the results obtained. The aqueous and aqueous aceto extracts of P. barbatus leaves showed MIC against E. coli, P. aeruginosa and two strains of MRSA ≥ 500 µg/mL, showing lower effectiveness than the extract under study [9].…”
Section: Antimicrobial Activitymentioning
confidence: 70%
“…In addition, the genus is recognized for its biological activities, such as antimicrobial, anticancer, antiparasitic, repellent, immunomodulating activity, among others. Its bioactivities are related to its content of phenolic compounds, proving to be rich in flavonoids, especially flavones, flavonols and flavonones, and phenolic acids, such as trans-rosmarinic acid [4,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The floral extract was the filtered and concentrated to dryness by using rotary evaporator. The obtained extract was dried (freeze drying) and stored at -12 °C until further analysis described by Cordeiro et al (2022) modified.…”
Section: Extract Productionmentioning
confidence: 99%
“…Natural products, especially those of plant origin, represent the main sources of active substances with potential therapeutic use and the oldest source of medicines ever used by humans (Moga et al, 2016;Cordeiro et al, 2021). Knowledge of the nutritional and medicinal properties of a country's biodiversity species, especially plants, has been the basis for the development of society and human survival, as they bring benefits to science and to the national bioeconomy (Rodrigues and De Simoni, 2010).…”
Section: Introductionmentioning
confidence: 99%